Respostas

2014-08-08T09:37:22-03:00
Substituindo x por -1 =
(3^-1.2) - (5^-1+1). (2^2.-1)=
3^-2 - 5^0 . 2^-2=
 1        1          1
----  -          .  -------  =
 3²                    2²

 1          1
----    -  ------ =    mmc = 36
 9            4

 4          9            5
----    - ------- = -  ------
 36        36          36
letra a
2014-08-08T11:25:22-03:00
 3^{x ^{2} }-5 ^{x + 1}. 2^{2x}
 . Para x = -1, temos:
 3^{(-1) ^{2} }-5 ^{(-1 + 1)}.2 ^{2.(-1)}
3-1. 2^{-2} = 3 - \frac{1}{4} =  \frac{(12-1)}{4}=  \frac{11}{4}
 
                     Resposta:   \frac{11}{4}